The Relationship Between Auditor Independence and Audit Quality: Evidence from Developing Economies - Manneh, Kekoto; Yuhertiana, Indrawati; Sholihatin, Endang (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
The primary purpose of this study is to explore the relationship between auditor independence and audit quality in developing economies by systematically reviewing 24 publications published between 2014 and 2025 from the Scopus database, following PRISMA guidelines. The study also used bibliometric analysis to provide a base for quantitative analysis from selected papers using VOSviewer and Biblioshiny (RStudio). The study employed various theories to examine the link between auditor independence and audit quality, elucidating how incentives, institutions, and stakeholders shape auditor conduct. These theories include agency theory, institutional theory, and stakeholder theory. Additionally, the study examines empirical evidence on the relationship between independence and quality in developing economies. It creates a conceptual framework that links this relationship through several moderating and mediating factors, including audit fees, non-audit services (NAS), tenure, regulations, and political connections. Findings of this study reveal that independence significantly influences audit quality, but its effectiveness depends heavily on vigorous regulatory enforcement, ethical commitment, and institutional support. The study has several limitations, including reliance on secondary data, publication bias, and the majority of the reviewed studies employing quantitative approaches, which have restricted our knowledge of the behavioral and ethical aspects of independence. It has been recommended that future researchers adopt mixed-methods approaches, conduct cross-sectional studies, and, most importantly, research trending topics such as digital audit technologies and ESG assurance in relation to data analytics, which are generating new threats to independence that are not covered by known frameworks.